Neuroprotective Properties of Chlorogenic Acid and 4,5-Caffeoylquinic Acid from Brazilian arnica (Lychnophora ericoides) after Acute Retinal Ischemia - Liberato, José Luiz; Rosa, Marcela Nunes; Miranda, Matheus C. Romeiro; Lopes, João Luís Callegari; Lopes, Norberto Peporine; Gobbo-Neto, Leonardo; Fontana, Andreia C. K.; dos Santos, Wagner Ferreira (Planta Medica, 2022)
Lychnophora is a genus of South American flowering plants in the daisy family, popularly known as “Brazilian arnica”. It is used in traditional medicine as an anti-inflammatory and analgesic agent, whose active components are derived from chlorogenic acid (CGA) and C-flavonoids. Since the drugs currently used are ineffective to treat glaucoma, agents with antioxidant and anti-inflammatory properties may represent new alternatives in preventing cellular lesions in retinal ischemia. In this study, we report the neuroprotective effects of CGA and 4,5-di-O-[E]-caffeoylquinic (CQA) acid, isolated from Lychnophora plants, in a rodent glaucoma model. Wistar rats were administered intravitreally with 10 µg CGA or CGA, and then subjected to acute retinal ischemia (ISC) by increasing intraocular pressure (IPO) for 45 minutes followed (or not) by 15 minutes of reperfusion (I/R). Qualitative and quantitative analyses of neurodegeneration were performed using hematoxylin-eosin or Fluoro-Jade C staining protocols. All retinas submitted to ISC or I/R exhibited matrix disorganization, pyknotic nuclei, and pronounced vacuolization of the cytoplasm in the ganglion cell layer (GCL) and inner nuclear layer (INL). Pretreatment with CGA or CQA resulted in the protection of the retinal layers against matrix disorganization and a reduction in the number of vacuolized cells and pyknotic nuclei. Also, pretreatment with CGA or CQA resulted in a significant reduction in neuronal death in the GCL, the INL, and the outer nuclear layer (ONL) after ischemic insult. Our study demonstrated that CGA and CQA exhibit neuroprotective activities in retinas subjected to ISC and I/R induced by IPO in Wistar rats.
Keywords: Lychnophora ericoides, compositae; Asteraceae; 4,5-di-O-[E]-caffeoylquinic acid; chlorogenic acid; acute rat retinal ischemia; neuroprotection